FILTERING CULTURAL INFLUENCES IN FOREIGN LANGUAGE LEARNING IN THE INDONESIAN CONTEXT: THE CONTROVERSY AND SUGGESTED ACTIONS - Ari Purnawan (Universitas Ahmad Dahlan)
There has been a prolonging controversy on why teachers need to filter the cultural load in foreign language learning. Some educators guarantee that the best way of learning a new language is by presenting the target language situations in the classroom, which usually includes the values, culture, habits, or ways of behaving and thinking of the target language users; however, some others believe that, for the sake of nation’s future and pride, they have to filter and block any influences that come from the value loads. Throughout the long history of foreign language learning approaches and methods, this issue has been one of their hot flavors. In fact, cultural contents are unavoidable in foreign language learning. Therefore, the type of culture to be included in the materials and the goal of study are two important aspects to consider (Kramsch, 2013). The paper aims to present ways that teachers can do to deal with the above issue. Involving culture in a selective manner may become a moderate compromise, and cautious actions in selecting the values to be loaded in the process of teaching and learning needs to be formulated and carefully listed. Some suggested items based on some intensive observations and teacher interviews are presented in the paper. It is expected that the culture issue in English language teaching settings develops into a good awareness of the importance of culture in language learning on the one hand, and of the preservation of own national identity and values on the other hand.